Parental involvement of high and low achievers in English language learning - q case study / Nor Fadillah Yaakub - Yaakub, Nor Fadillah (2009)
The importance of the role of parents in their children’s education is not a new concept. Parents have been recognized as their children’s first teachers since the beginning of time. Research in the area of parental involvement indicates that children whose parents are involved and provide help to them at home and stay in touch with the school score higher than children whose parents are not involved. The present study seeks to identify the type of parental involvement employed by both parents of high and low achievers in supporting their English Language learning. The level of achievement in this study is based on the results of their PMR English paper. According to past researches, parental involvement activities in the children’s learning at home are of different ways and to varying degrees. This study hopes to uncover what type of parental involvement activities in the home that can have impact on the levels of attainment particularly in the process of English Language learning. The theoretical basis of the study is based on the framework proposed by Epstein (2002) where she states that there are two aspects of parental involvement which are: home -based Involvement and school-based Involvement. For the purpose of this study, home-based involvement will be measured by three dimensions namely; learning support, home enrichment, and home limitation. While schoolbased involvement will be measured by school communication, and school activities. The present study adopted a mixed method where data obtained was derived from two types of instruments: survey questionnaire and semi-structured interviews. A total of 60 students reported the extent to which their parents have been involved in these aspects of parental activities. Overall results from the present study revealed that activities in terms of ‘learning support’, ‘home enrichment’ and ‘home limitation’ were common practices adopted by the parents of high achievers. On the other hand, the parents of low achievers adopted a laisser-faire attitude in their involvement. Implication for the study included the need to conduct needs analysis identifying what are the concerns and issues surrounding parent involvement in the language education of their children. In addition, academicians could develop a repertoire of strategies in English language learning designed to increase parental involvement at school and at home. Finally, academicians, school administrators and stakeholders should work together in creating comprehensive program of partnership to support the interaction of ideas and experiences centred on language learning.